Of Hiwar Texts Among MTS Students: Analysis Of Student Abilities Class IX-2 MTS Al-Ittihadiyah Mamiyai - Sartika Alpianti Manurung; Mutia Syahdina; Muhammad Wildan Fikri Azkia; Sahkholid Nasution (Sean Institute, 2024)
In the context of language learning, translation is very important. Translating hiwar texts is often a challenge for students in class IX-2, especially in understanding the context of the intended meaning in a conversational sentence. This study aims to find out the problems faced by students when translating hiwar texts in Arabic language learning. The method used in this research is qualitative method with descriptive analysis as the approach. Data were collected using literature review, interviews and participatory observation, and the data analysis technique used was descriptive analysis. The results of this study show that students face two translation problems, namely linguistic and non-linguistic problems.